Method of Economic Order Quantity (EOQ) as an Analysis of Raw Material Inventory Control at PT Metalindo Main Engineering - Lugina Lestari; Aulia Fashanah Hadining (School of Industrial and System Engineering, Telkom University, 2022)
PT Metalindo Teknik Utama is a company engaged in Manufacturing (body of a car). So far, in managingraw material inventories, the company used simple method with buy raw material if the inventory is out ofstock. The use of this method resulted in the cost of managing the raw materials incurred is still relativelyexpensive. This study aims to analyze the cost of inventory management based on the Economic OrderQuantity method and compare the costs of inventory management implemented by the company in 2020.The data is taken based on the company's annual financial statements prepared in 2020. The data isanalyzed using the EOQ formula. Results of the research in the form off O2, the number of economicalorders according to EOQ is 141 tube with a raw material inventory cost of Rp. 6,771,277 while accordingto the company's method of Rp. 25,542,451 then obtained savings or a difference of Rp. 18,771,174. InCO2 the number of economical orders according to EOQ is 130 tube with a raw material inventory cost ofRp. 6,770.777, while according to the company's method it is Rp. 23,601,184 then the savings ordifference is Rp. 16,830.407. For LPG, the number of economical orders according to EOQ is 31 tubeswith a raw material inventory cost of Rp. 1,447,350 while according to the company's method it is Rp.4,631,372 then the savings or difference is Rp. 3,184,022.